The C-X-C Motif Chemokine Ligand 1 Sustains Breast Cancer Stem Cell Self-Renewal and Promotes Tumor Progression and Immune Escape Programs - Ciummo, Stefania Livia; D’Antonio, Luigi; Sorrentino, Carlo; Fieni, Cristiano; Lanuti, Paola; Stassi, Giorgio; Todaro, Matilde; Di Carlo, Emma (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer (BC) mortality is mainly due to metastatic disease, which is primarily driven by cancer stem cells (CSC). The chemokine C-X-C motif ligand-1 (CXCL1) is involved in BC metastasis, but the question of whether it regulates breast cancer stem cell (BCSC) behavior is yet to be explored. Here, we demonstrate that BCSCs express CXCR2 and produce CXCL1, which stimulates their proliferation and self-renewal, and that CXCL1 blockade inhibits both BCSC proliferation and mammosphere formation efficiency. CXCL1 amplifies its own production and remarkably induces both tumor-promoting and immunosuppressive factors, including SPP1/OPN, ACKR3/CXCR7, TLR4, TNFSF10/TRAIL and CCL18 and, to a lesser extent, immunostimulatory cytokines, including IL15, while it downregulates CCL2, CCL28 and CXCR4. CXCL1 downregulates TWIST2 and SNAI2, while boosts TWIST1 expression in association with the loss of E-Cadherin, ultimately promoting BCSC epithelial-mesenchymal transition. Bioinformatic analyses of transcriptional data obtained from BC samples of 1084 patients, reveals that CXCL1 expressing BCs mostly belong to the Triple-Negative subtype, and that BC expression of CXCL1 strongly correlates with that of pro-angiogenic and cancer promoting genes, such as CXCL2-3-5-6, FGFBP1, BCL11A, PI3, B3GNT5, BBOX1 and PTX3, suggesting that the CXCL1 signaling cascade is part of a broader tumor-promoting signaling network. Our findings reveal that CXCL1 functions as an autocrine growth factor for BCSCs and elicits primarily tumor progression and immune escape programs. Targeting the CXCL1/CXCR2 axis could restrain the BCSC compartment and improve the treatment of aggressive BC.